The devil is in the shadow: do institutions affect income and productivity or only official income and official productivity? - Dreher, Axel; Méon, Pierre-Guillaume; Schneider, Friedrich (KOF working papers, 2007)
This paper assesses the relationship between institutions, output, and productivity, when official output is corrected for the size of the shadow economy. Our results confirm the usual positive impact of institutional quality on official output and total factor productivity, and its negative impact on the size of the underground economy. However, once output is corrected for the shadow economy, the relationship between institutions and output becomes weaker. The impact of institutions on total ("corrected") factor productivity even becomes insignificant. Differences in corrected output must then be attributed to differences in factor endowments. These results survive several tests for robustness. -- shadow economy ; income ; aggregate productivity ; development accounting